Response of human bone synthetic under impact load using finite element method - Mohamad Shahnaz, Samsul Bahari (2009)
Commercial bone synthetic can be considered as a composite material where testing can be carried out to find out its mechanical properties. Generally there is lack of information about the properties of bone synthetic although it has been extensively used in caring human bone defect and injuries. Particularly, its real strength to external load, particularly sudden load is unknown. This project focus on identify the response of human bone synthetic under impact loading using finite element method. The geometry of finite element model was constructed in SolidWorks mechanical CAD package. The micron size of pores was created spline-feature-extrude method to include porosity as close as possible to that of the actual bone. The computational model was analyzed using ALGOR. The appropriate model was determined through the mesh convergence analysis for better accuracy. The results were is good agreement in term of location of their concentration. The proposed finite element model can be used to analyze the response of the human bone under various loading.